2010
DOI: 10.1007/s10658-010-9668-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rice development on the function of bacterial blight resistance genes

Abstract: Disease resistance genes most commonly used in breeding programs are single, dominant genes with relative effectiveness that is sometimes influ-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
8
0
2
Order By: Relevance
“…Dominant but un-cloned R gene Xa7 was first identified in DV85 rice cultivar and was reported to be predominate in Aus cultivars of Bangladesh [18,75,76]. Though it is not cloned yet, its durable resistance and effectiveness in high temperature makes it a desirable target gene in modern breeding programs especially in tropical country like Bangladesh [49,77]. In the present study, we identified maximum 83.78% germplasm (62 out of 74) which carries Xa7 gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dominant but un-cloned R gene Xa7 was first identified in DV85 rice cultivar and was reported to be predominate in Aus cultivars of Bangladesh [18,75,76]. Though it is not cloned yet, its durable resistance and effectiveness in high temperature makes it a desirable target gene in modern breeding programs especially in tropical country like Bangladesh [49,77]. In the present study, we identified maximum 83.78% germplasm (62 out of 74) which carries Xa7 gene.…”
Section: Discussionmentioning
confidence: 99%
“…The STS markers utilized in the study were found highly efficient to identify the resistant genes. Dominant resistant gene Xa4, first reported by [48], functioned via cell wall-associated kinase synthesis and confers a race-specific but plant growth stage nonspecific resistance towards Xoo strains [49][50][51]. Moreover, [51] deciphered the role of Xa4 gene in improving certain quantitative traits such as, plant height.…”
Section: Discussionmentioning
confidence: 99%
“…Xa7 gene is well known for conferring durable resistance against bacterial leaf blight, which has been verified by a 10-year cropping period (Webb et al 2010). Furthermore, increased effectiveness has been reported for Xa7-mediated resistance under high temperature and drought stresses (Dossa et al 2020).…”
Section: Introductionmentioning
confidence: 90%
“…oryzae (Xoo) have become important models for understanding the fundamental aspects of plant disease resistance and bacterial pathogenesis, as well as other aspects of plant and microbial biology, with implications for innate animal immunity too (Niño-Liu et al 2006). Xa4 gene mediates a race-specific and durable resistance to Xoo at all stages of rice growth in many countries (Webb et al 2010). Xa4 gene was first incorporated into commercial rice varieties in the early 1979s and has been one of the most widely exploited resistance genes in breeding programs in at least 54 Asian, African, South American, and Mesoamerican countries (Khush and Virk 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Galur isogenik bermanfaat dalam monitoring keparahan serangan dan distribusi ras Xoo (Ogawa et al, 1988). Di samping itu, galur-galur isogenik juga dapat digunakan sebagai standar diferensial untuk mengetahui perbedaan respons patogenisitas atau virulensi suatu ras (Hayashi dan Fukuta, 2007;Khoshkdaman et al, 2012;Loan et al, 2006;Noh et al, 2016;Tsunematsu et al, 2000) dan untuk evaluasi ketahanan galur hasil persilangan (silang balik) dalam rangka perakitan varietas tahan HDB (Webb et al, 2010).…”
Section: Pendahuluanunclassified